Tweens’ Wishful Identification and Parasocial Relationships With YouTubers - Tolbert, Amanda N.; Drogos, Kristin L. (Frontiers in Psychology, 2019)
Children between the ages of 9 and 12 - commonly called tweens - are one of the fastest growing audiences for YouTube content. The current study explores how tweens are watching YouTube and the nature of their parasocial relationships and wishful identification with their favorite YouTube personalities. Results show that tweens identified gender-congruent YouTubers as their favorite. Moreover, tweens perceived male and female YouTubers to have different attributes. For instance, male YouTubers were rated as more violent than female YouTubers, and female YouTubers were rated as more attractive and popular than male YouTubers. Gender also played a role in attachment patterns. Tween boys’ wishful identification was predicted by YouTubers who were violent and funny and their parasocial relationships were predicted by YouTubers who were funny, successful, and attractive. Meanwhile, tween girls’ wishful identification was predicted by YouTubers’ who were funny, and their parasocial relationships were predicted by YouTubers’ who were funny and popular. Results are discussed in terms of gender socialization theory.